Female ascetics in Hinduism - Denton, Lynn Teskey, 1949-1995 (SUNY series in Hindu studies., 2004)
"Female Ascetics in Hinduism provides an account of the lives of women renouncers - women who renounce the world to live ascetic spiritual lives - in India. The author approaches the study of female asceticism by focusing on features of two dharmas, two religiously defined ways of life: that of woman-as-householder and that of the ascetic, who, for various reasons, falls outside the realm of householdership. The result of fieldwork conducted in Varanasi (Benares), the book explores renouncers' social and personal backgrounds, their institutions, and their ways of life. Offering a first-hand look at and an insightful analysis of this little-known world, this book will be indispensable to those interested in female asceticism in the Hindu tradition and women's spiritual lives around the world."--Jacket